Criteria Analysis and Application of Analytical Hierarchy Process (AHP) In Determining Road Maintenance Priorities on Cokroaminoto Bojonegoro Road Section - Arifin, Miftakhul; Marleno, Risma; Oetomo, Wateno (Asian Journal of Social and Humanities, 2025)
This study aims to develop a systematic approach for prioritizing road maintenance on Cokroaminoto Road in Bojonegoro by combining the Analytical Hierarchy Process (AHP) with PKRMS data. The research identifies eight key criteria essential for prioritizing maintenance activities, including road damage, traffic volume, safety, construction costs, implementation duration, accessibility, and weather conditions. AHP was used to assign weights to these criteria, with safety emerging as the most critical factor. The results show that road sections with high traffic intensity and significant deterioration are prioritized for preventive maintenance, especially in areas with high accident risks. By integrating technical data from the PKRMS with the AHP methodology, this study offers a transparent and objective decision-making model for road management. The findings highlight the importance of focusing on preventive maintenance to mitigate future rehabilitation costs and extend the service life of roads. This research provides valuable insights for efficient resource allocation and offers a replicable model for road infrastructure management in other regions with similar challenges.